Diseño de un sistema de climatización para un edificio en Prince George, Columbia Británica – Canadá basado en la propuesta 2021 design competition – ASHRAE (2021)
Based on the competition proposal proposed by ASHRAE "2021 DESIGN COMPETITION", which focuses on a new building on a higher education campus located in Prince George, British Columbia, Canada, for which the selection and final design of the HVAC system must be made. Along with floor plans and relevant information regarding the construction and the conditions required for comfort, a diagnosis of initial parameters is made where the conditions to which the building will be exposed in terms of climatic conditions, regarding its location, the owner's requirements and applicable standards for the development of the project are established.